Discretionary Accruals: Contribution Of Quality Environmental Disclosures, Corporate Governance, And Assimetric Information - Bahtiar Effendi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
The purpose of this research is to determine the impact of the quality environmental disclosure, corporate governance, and assimetric information on discretionary accruals. In this study, the population is mining companies that implement PROPER and are listed on the Indonesia Stock Exchange between 2016 and 2020. Purposive sampling was used to obtain data from 47 different companies. Multiple linear regression analysis was performed to analyze the data. The quality of environmental disclosure has impact on discretionary accruals, corporate governance has impact on discretionary accruals, assimetric information has impact on discretionary accruals. Simultaneously, the findings of the quality of environmental disclosure, corporate governance and assimetric information has impact on discretionary accruals.